The greatest short stories of anton chekhov - Chekhov, Anton Pavlovich; Garnett, Constance (New Delhi, India : Fingerprint! Classics, 2023)
The Death of a Government Clerk -- Joy -- In the Graveyard -- Small Fry -- A Malefactor -- The Huntsman -- A Dead Body -- Oh! The Public -- A Blunder -- Anyuta -- The Witch -- Easter Eve -- A Day in the Country -- The Chemist's Wife -- A Trifle from Life -- The Orator -- Who Was to Blame? -- Love -- Misery -- Vanka -- The Lottery Ticket -- Typhus -- In Passion Week -- A Happy Ending -- A Story without a Title -- Sleepy -- The Bet -- The Princess -- A Dreary Story -- Gusev -- Peasant Wives -- Ward No. 6 -- In Exile -- After the Theatre -- The Black Monk -- Rothschild's Fiddle -- The Student -- 'Anna on the Neck' -- An Artist's Story -- The Schoolmistress -- Peasants -- The Man in a Case -- Gooseberries -- About Love -- The Darling -- At Christmas Time -- On Official Duty -- The Lady with the Dog -- The Bishop -- Betrothed
AAL
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Chekhov, Anton Pavlovich, -- 1860-1904; Short stories, Russian -- 19th century; Man-woman relationships -- Fiction; Russia -- Social life and customs -- 19th century -- Fiction; Short stories